WISKUNDE
NOG OEFENINGE

Afgeleides - gebruik die reëls : antwoorde.

MATHEMATICS
MORE EXERCISES

Derivatives - use the rules : answers.

Vraag / Question  1

dy
1.1  ─── =  (3)x3 − 1
dx

=  3x2                                           V/Q. 1.1

dy
1.3  ─── =  (7)x7 − 1  +  (3)x3 − 1
dx

=  7x6  +  3x2                                V/Q. 1.3

dy
1.5  ─── =  (4)x4 − 1  −  (2)x2 − 1
dx

=  4x3  −  2x                                 V/Q. 1.5

dy
1.7  ─── =  2(3)x3 − 1  +  3(2)x2 − 1
dx

=  6x2  +  6x                                 V/Q. 1.7

dy
1.9  ─── =  5(4)x4 − 1  −  4(3)x3 − 1  +  8(1)x1 − 1
dx

=  20x3  −  12x2  +  8                   V/Q. 1.9

dy
1.11  ─── =  7(3)x2  −  3(2)x  +  2(1)
dx

=  21x2  −  6x  +  2                    V/Q. 1.11

__
1.13  y =  √x   =  x1/2

dy
─── =  (½)x½ − 1    =  ½x−½
dx

1
=  ───                                     V/Q. 1.13
2√x

___
1.15  y =  √2x3   =  √2 × x3/2

dy        √2     3                          3√2
─── =  ── × ─ ×  x3/2 − 1    =  ─── × x½
dx         1      2                            2

___

3√2x
=  ──────                            V/Q. 1.15
2

4
1.17  y =  ──   =  4x−1
x

dy
─── =  4(−1)x−2    =  −4 x−2
dx

4
=  ─  ───                              V/Q. 1.17
x2

6
1.19  y =  ──   =  6x−3
x3

dy
─── =  6(−3)x−4    =  −18 x−4
dx

18
=  ─  ───                              V/Q. 1.19
x4

x6         x4
1.21  y =  ──  ─  ──
9          8

dy         1        6                    1        4
─── =  ── ×  ── × x5   ─   ── ×  ── × x3
dx         9        1                    8        1

2x5          x3
=  ───  ─  ───                     V/Q. 1.21
3            2

x5         2x3
1.23  y =  ──  ─  ──
15          6

dy         1        5                    2        3
─── =  ── ×  ── × x4   ─   ── ×  ── × x2
dx        15       1                    6        1

x4
=  ───  ─  x2                         V/Q. 1.23
3

3
1.25  y =  ───   =  3x−1/2
√x

dy
─── =  3(−½)x−3/2    =  −(3/2) x−3/2
dx

3
=  ─  ───                              V/Q. 1.25
2√x3

−3
1.27  y =  ───  −    x10     =  ─  3x−½   −  x10
√x

dy
─── =  ─3(−½)x−3/2    ─   10x9
dx

3
=  ───   −  10x9                     V/Q. 1.27
2√x3

___
√3x4         5
1.29  y =  ───  −  ───      =  ⅓(3x4)½   −  (5/3)x−5
3          3x5

dy
─── =   ⅓(3½)(2)x1    ─   (5/3)(−5)x−6
dx

2√3 x            25
=   ─────   +  ───              V/Q. 1.29
3                3x6

√x  −  4
1.31  y =  ──────      =  1   −  4x−½
√x

dy
─── =   0    ─   4(−½)x−3/2
dx

2
=   ────                                V/Q. 1.31
√x3

3x  +  8
1.33  y =  ──────      =  3x½   +  8x−½
√x

dy
─── =   3(½)x−½    +   8(−½)x−3/2
dx

3                 4
=   ────   −   ────             V/Q. 1.33
2√x             √x3

x2  −  3x  −  2
1.35  y =  ──────      =  ½x  −  (3/2)   −  x−1
2x

dy
─── =   ½(1)x0    −   0   −   (−1)x−2
dx

1                1
=   ───   +   ────
2               x2

V/Q. 1.35

1.37  y =  (x − 1)(x + 5)    =  x2  +  4x  −  5

dy
─── =  (2)x1 + 4(1)x0 − 0
dx

=   2x + 4                                 V/Q. 1.37

1.39  y =  (2x + 1)(x + 3)    =  2x2  +  7x  +  3

dy
─── =  2(2)x1 + 7(1)x0 − 0
dx

=   4x + 7                                V/Q. 1.39

1.41  y =  (2x + 3)(4x + 5)    =  8x2  +  22x  +  15

dy
─── =  8(2)x1 + 22(1)x0 − 0
dx

=   16x + 22                            V/Q. 1.41

1.43  y =  (x + 2)2    =  x2  +  4x  +  4

dy
─── =  (2)x1 + 4(1)x0 − 0
dx

=   2x + 4                                V/Q. 1.43

1.45  y =  (x + 4)2    =  x2  +  8x  +  16

dy
─── =  (2)x1 + 8(1)x0 − 0
dx

=   2x + 8                                 V/Q. 1.45

1.47  y =  (2x3 − 3)(3x4 + 3)    =  6x7  −  9x4  +  6x3  −  9

dy
─── =  6(7)x6 − 9(4)x3 + 6(3)x2  − 0
dx

=   42x6 − 36x2 + 18x2            V/Q. 1.47

1.49  y =  (x − 3)(x + 2)(x + 5)    =  x3  +  4x2  −  11x  −  30

dy
─── =  (3)x2 − 4(2)x − 11(1)x0  − 0
dx

=   3x2 − 8x − 11                     V/Q. 1.49

6x5 + 4x3 − 8x2 + 10x
1.51  y =  ────────────────
2x

=  3x4 + 2x2 − 4x  +  5            x ≠ 0

dy
─── =  3(4)x3 + 2(2)x1 − 4
dx

=   12x3 + 4x − 4                    V/Q. 1.51

2x4 − 8x3 + 4x2
1.53  y =  ───────────
2x2

=  x2 − 4x + 2            x ≠ 0

dy
─── =  (2)x1 − (4)x0 − 0
dx

=   2x − 4                                V/Q. 1.53

x2  −  9
1.55  y =  ───────
x  +  3

(x − 3)(x + 3)
=  ─────────
x  +  3

=  x  −  3                  (x + 3)  ≠ 0

dy
─── =  x0 − 0
dx

=   1                                         V/Q. 1.55

x2  −  25
1.57  y =  ──────
x  +  5

(x − 5)(x + 5)
=  ─────────
x  +  5

=  x  −  5                  (x + 5)  ≠ 0

dy
─── =  x0 − 0
dx

=   1                                         V/Q. 1.57

9x2  −  25
1.59  y =  ────────
3x  −  5

(3x − 5)(3x + 5)
=  ─────────
3x  −  5

=  3x  +  5                  (3x − 5)  ≠ 0

dy
─── =  3(1)x0 − 0
dx

=   3                                         V/Q. 1.59

x2  −  8x  +  12
1.61  y =  ───────────
x  −  2

(x − 2)(x − 6)
=  ─────────
x  −  2

=  x  −  6                  (x − 2)  ≠ 0

dy
─── =  1x0 − 0
dx

=   1                                        V/Q. 1.61

x2  −  8x  +  15
1.63  y =  ───────────
x  −  5

(x − 3)(x − 5)
=  ─────────
x  −  5

=  x  −  3                  (x − 5)  ≠ 0

dy
─── =  1x0 − 0
dx

=   1                                         V/Q. 1.63

4x2  +  8x  +  3
1.65  y =  ───────────
2x  +  5

(2x + 1)(2x + 3)
=  ─────────
2x  +  1

=  2x  +  3                  (2x + 1)  ≠ 0

dy
─── =  2(1)x0 + 0
dx

=   2                                         V/Q. 1.65

dy
1.2  ─── =  (8)x8 − 1
dx

=  8x7                                           V/Q. 1.2

dy
1.4  ─── =  (5)x5 − 1  +  (2)x2 − 1
dx

=  5x4  +  2x                                 V/Q. 1.4

dy
1.6  ─── =  (3)x3 − 1  −  3(2)x2 − 1
dx

=  3x2  −  6x                                 V/Q. 1.6

dy
1.8  ─── =  4(5)x5 − 1  −  2(3)x3 − 1
dx

=  20x4  −  6x2                        V/Q. 1.8

dy
1.10  ─── =  4(5)x5 − 1  −  2(3)x3 − 1
dx

=  20x4  −  6x2                        V/Q. 1.10

dy
1.12  ─── =  4(3)x2  −  3(2)x  +  2(1)
dx

=  12x2  −  6x  +  2                       V/Q. 1.12

___
1.14  y =  √4x3   =  √4 × x3/2

dy        2    3
─── =  ─ × ─ ×  x3/2 − 1    =  3x½
dx        1    2

=  3√x                                          V/Q. 1.14

___
1.16  y =  √3x5   =  √3 × x5/2

dy        √3     5
─── =  ── × ─ ×  x5/2 − 1    =  5(√3)x3/2
dx         1      2

___
=  5√3x3                                       V/Q. 1.16

8
1.18  y =  ──   =  8x−2
x2

dy
─── =  8(−2)x−3    =  −16 x−3
dx

16
=  ─  ───                                   V/Q. 1.18
x3

7
1.20  y =  ──   =  7x−5
x5

dy
─── =  7(−5)x−6    =  −35 x−6
dx

35
=  ─  ───                                   V/Q. 1.20
x6

x3         x2
1.22  y =  ──  ─  ──
4          6

dy         1        3                    1        2
─── =  ── ×  ── × x3   ─   ── ×  ── × x
dx         4        1                    6         1

3x3          x
=  ───  ─  ───                         V/Q. 1.22
4            3

3x4      5x3
1.24  y =  ──  ─  ──
2          3

dy         3        4                    5        3
─── =  ── ×  ── × x3   ─   ── ×  ── × x2
dx         2        1                    3         1

=  6x3  ─  5x2                               V/Q. 1.24

1
1.26  y =  ───   =  ½x−1/2
2√x

dy
─── =  ½(−½)x−3/2    =  −¼ x−3/2
dx

1
=  ─  ───                                   V/Q. 1.26
4√x3

√x           1
1.28  y =  ───  −  ───     =  ⅓x½   −  (1/7)x−4
3           7x4

dy
─── =  ⅓(½)x−½    ─   (1/7)(−4)x−5
dx

1             4
=  ─  ───   +  ───                    V/Q. 1.28
6√x           7x5

___
√x5           9
1.30  y =  ───  −  ───     =  2x5/2   −  (9/8)x−6
0,5           8x6

dy
─── =  2(5/2)x3/2    ─   (9/8)(−6)x−7
dx

27
=   5√x3   +  ───                       V/Q. 1.30
4x7

4              x2
1.32  y =  ───   ─   ───     =  4x−½   −  (1/9)x2
√x              9

dy
─── =  4(−½)x−3/2 − (1/9)(2)x1
dx

2             2x
=   ───   −   ───                       V/Q. 1.32
√x3            9

x3             6
1.34  y =  ───   ─   ───     =  (1/6)x3   −  x−2
6              x2

dy
─── =  (1/6)(3)x2 − (−2)x−3
dx

2
=   ½x2   +   ───                        V/Q. 1.34
x3

1  −  2x  +  √x
1.36  y =  ──────────      =  x−2  −  2x−1   +  x−3/2
x2

dy
─── =   (−2)x−3    −   2(−1)x−2   +   (−3/2)x−5/2
dx

2                2                3
=   ─ ───   +   ────   −   ────
x3              x2              2√x5

V/Q. 1.36

1.38  y =  (x − 3)(x + 2)    =  x2  −  x  −  6

dy
─── =  (2)x1 − (1)x0 − 0
dx

=   2x − 1                                    V/Q. 1.38

1.40  y =  (3x − 4)(x + 5)    =  3x2  +  11x  −  20

dy
─── =  3(2)x1 + 11(1)x0 − 0
dx

=   6x + 11                                  V/Q. 1.40

1.42  y =  (2x − 3)(5x + 2)    =  10x2  −  11x  −  6

dy
─── =  10(2)x1 − 11(1)x0 − 0
dx

=   20x − 11                                V/Q. 1.42

1.44  y =  (x − 3)2    =  x2  −  6x  +  9

dy
─── =  (2)x1 − 6(1)x0 + 0
dx

=   2x − 6                                     V/Q. 1.44

1.46  y =  (3x + 2)2    =  9x2  +  12x  +  4

dy
─── =  9(2)x1 + 12(1)x0 + 0
dx

=   18x + 12                                V/Q. 1.46

1.48  y =  (4x2 − 5)(3x4 + 4)    =  12x6  −  15x4  +  16x2  −  20

dy
─── =  12(6)x5 − 15(4)x3 + 16(2)x1 − 0
dx

=   72x5 − 60x3 + 32x                 V/Q. 1.48

1.50  y =  (3x3 − 7)(5x4 + 3)    =  15x7  −  35x4  +  9x3  −  21

dy
─── =  15(7)x6 − 35(4)x3 + 9(3)x2 − 0
dx

=   105x6 − 140x3 + 27x2           V/Q. 1.50

9x7 − 18x5 + 6x3 − 24x
1.52  y =  ────────────────
3x

=  3x6 − 6x4 + 2x2 − 8              x ≠ 0

dy
─── =  3(6)x5 − 6(4)x3 + 2(2)x
dx

=   18x5 − 24x3 + 4x;                 V/Q. 1.52

4x3 + 8x2 − 12x
1.54  y =  ────────────
4x

=  x2 + 2x − 3              x ≠ 0

dy
─── =  (2)x1 + (2)x0 + 0
dx

=   2x + 2                                    V/Q. 1.54

x2  −  16
1.56  y =  ───────
x  −  4

(x − 4)(x + 4)
=  ─────────
x  −  4

=  x  +  4                  (x − 4)  ≠ 0

dy
─── =  x0 + 0
dx

=   1                                                V/Q. 1.56

4x2  −  9
1.58  y =  ───────
2x  −  3

(2x − 3)(2x + 3)
=  ─────────
2x  −  3

=  2x  +  3                  (2x − 3)  ≠ 0

dy
─── =  2x0 + 0
dx

=   2                                               V/Q. 1.58

25x2  −  16
1.60  y =  ─────────
5x  +  4

(5x − 4)(5x + 4)
=  ─────────
5x  +  4

=  5x  −  4                  (5x + 4)  ≠ 0

dy
─── =  5x0 + 0
dx

=   5                                                V/Q. 1.60

x2  +  5x  +  6
1.62  y =  ──────────
x  +  2

(x + 2)(x + 3)
=  ─────────
x  +  2

=  x  +  3                  (x + 2)  ≠ 0

dy
─── =  x0 + 0
dx

=   1                                               V/Q. 1.62

x2  −  6x  −  7
1.64  y =  ──────────
x  +  1

(x − 7)(x + 1)
=  ─────────
x  +  1

=  x  −  7                  (x + 1)  ≠ 0

dy
─── =  x0 + 0
dx

=   1                                               V/Q. 1.64

6x2  −  7x  −  5
1.66  y =  ───────────
5  −  3x

(3x − 5)(2x + 1)
=  ───────────
−(3x  −  5)

=  −2x  −  1                  (3x − 5)  ≠ 0

dy
─── =  −2x0 − 0
dx

=   −2                                            V/Q. 1.66

2.1  f(x) =  x4

f'(x) =  4x3                                            V/Q. 2.1

2.3  f(x) =  3x4  +  1

f'(x) =  4(3)x3    =  12x3                       V/Q. 2.3

2.5  f(x) =  3x6  +  2x3  −  9x  −  4

f'(x) =  18x5 + 6x2 − 9                          V/Q. 2.5

2.7  f(x) =  √(3x)

=  √3 × x½

f'(x) =  (√3)(½)x−½

√3
=  ───                                          V/Q. 2.7
2√x

8
2.9  f(x) =  ───         =  8 x−2
x2

f'(x) =  (8)(−2)x−3

16
=  ─  ───                                     V/Q. 2.9
x3

6
2.11  f(x) =  ───         =  6x−3
x3

f'(x) =  (6)(−3)x−4

18
=  ─  ───                                     V/Q. 2.11
x4

1
2.13  f(x) =  ───         =  ½x−½
2√x

f'(x) =  (½)(−½)x−3/2

1
=  ─  ───                                    V/Q. 2.13
4√x3

4√x  −  x
2.15  f(x) =  ───────         =  4  −  x½
√x

f'(x) =  0  −  (½)x−½

1
=  ─  ───                                    V/Q. 2.15
√x

1
2.17  f(x) =  ───  +  √x         =  x−½  +  x½
√x

f'(x) =  (−½)x−3/2  +  (½)x−½

1               1
=  ─  ───    +   ───                    V/Q. 2.17
2√x3          2√x

2.19  f(x) =  (x − 6)2

=  x2  −  12x  +  36

f'(x) =  2x  −  12                                    V/Q. 2.19

2.21  f(x) =  (2x − 3)2

=  4x2  −  12x  +  9

f'(x) =  8x  −  12                                   V/Q. 2.21

2.23  f(x) =  (4x + 3)3

=  16x2  +  24x  +  9

f'(x) =  32x  +  24                                 V/Q. 2.23

x3 − 4x2 − 3x  + 18
2.25  f(x) =  ─────────────
x  +  2

(x + 2)(x2 − 6x + 9)
=  ─────────────
x  +  2
=  x2  −  6x  +  9

f'(x) =  2x  −  6                                          V/Q. 2.25

2.2  f(x) =  2x3

f'(x) =  6x2                                            V/Q. 2.2

2.4  f(x) =  2x5  −  6

f'(x) =  2(5)x4    =  10x4                       V/Q. 2.4

2.6  f(x) =  x5  +  4x3  −  7x2  −  6x  +  12

f'(x) =  5x4 + 12x2 − 14x − 6                V/Q. 2.6

2.8  f(x) =  √x3

=  x3/2

f'(x) =  (3/2)x½

3√x
=  ───                                          V/Q. 2.8
2

3
2.10  f(x) =  ───      =  (3/2)x−3
2x3

f'(x) =  (3/2)(−3)x−2

9
=  ─  ────                                 V/Q. 2.10
2x2

3
2.12  f(x) =  ───       =  3x−½
√x

f'(x) =  3(−½)x−3/2

3
=  ─  ────                                  V/Q. 2.12
2√x3

−3
2.14  f(x) =  ───  −  x10   =  −3x−½  −  x10
√x

f'(x) =  −3(−½)x−3/2  −  10x9

3
=  ────  −  10x9                         V/Q. 2.14
2√x3

2  −  x
2.16  f(x) =  ─────  −  ∛x    = (2/5)x−½ − (1/5)x½  − x
5√x

f'(x) =  (2/5)(−½)x−3/2  −  (1/5)(½)x−½  −  ⅓x(−⅔)

=  ─ (⅕)x−3/2  −  (1/10)x−½  −  (⅓)x−⅔

1          1              1
= ─ ─── ─ ───  ─  ────      V/Q. 2.16
5√x3     10√x      3 ∛(x2)

4
2.18  f(x) =  (3√x  +  ───)2
√x

2 × 3 × 4 × √x            42
=  (3√x)2  +  ──────────  +  ────
√x                    (√x)2

16
=  9x  +  24  +  ───        =  9x  +  24  +  16x−1
x

f'(x) =  9(1)  +  0  +  16(−1)x−2

16
=  9  −  ───                               V/Q. 2.18
x2

2.20  f(x) =  (4x − 5)2

=  16x2  −  40x  +  25

f'(x) =  32x  −  40                              V/Q. 2.20

2.22  f(x) =  (3x − 4)2

=  9x2  −  24x  +  16

f'(x) =  18x  −  24                              V/Q. 2.22

2.24  f(x) =  (2x − 3)3

=  (2x − 3)(4x2  −  12x  +  9)

=  8x3  −  36x2  +  54x  −  27

f'(x) =  24x2  −  72x  +  54                V/Q. 2.24

8x3   −  1               (2x − 1)(4x2 + 2x + 1)
2.26  f(x) =  ───────        =  ──────────────
2x  −  1                           2x  −  1

=  4x2  +  2x  +  1

f'(x) =  8x  +  2                                  V/Q. 2.26